CARING KELUARGA DENGAN KEJADIAN JATUH PADA LANSIA (Family Caring And Fall Incident On Eldery) - ISWATI, . (JURNAL NERS LENTERA, 2017)
Introduction: The progress in the health sector, the increasing welfare of the people can increase life expectancy, causing the number of the elderly population to increase every year. Seniors experience a decrease in the body's ability to adapt to the environment, so the risk of falling. Caring a family is what the elderly needs to prevent injuries and trauma from falling. Method: This research is correlation research by using cross sectional approach. The independent variable is caring family, while the dependent variable is the fall incident. Sampling was done in RW 07 Kelurahan Gading Kecamatan Tambaksari Surabaya by using technique